1997
DOI: 10.1111/j.1467-8624.1997.tb01957.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Pretend Play in Korean- and Anglo-American Preschoolers

Abstract: Ninety-two preschoolers (46 Anglo- and 46 Korean-American) were observed during free play activities and videotaped in an experimental toy play setting. Cultural differences were examined in the frequency of social pretend play, communicative strategies, and pretend play themes. Anglo-American children engaged in more pretend play during free play activities than Korean-American children. In the experimental setting, there were no cultural differences in the frequency of pretend play; however, there were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 21 publications
2
44
0
1
Order By: Relevance
“…Consistent with the majority of studies on preschool children's pretend play (e.g., Connolly & Doyle, 1984;Farver & Shin, 1997;Howes et al, 1989;Pellegrini & Perlmutter, 1989;Rubin & Maioni, 1975), but contrary to others (e.g., Lindsey & Mize, 2001;Rubin et al, 1978;Weinberger & Starkey, 1994), we found no gender differences in pretend play. Examination of the studies that have reported gender differences in pretend play reveal that most, although by no means all (see Jones & Glenn, 1991;Weinberger & Starkey, 1994, for exceptions), used semistructured and laboratory settings to observe children's play.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consistent with the majority of studies on preschool children's pretend play (e.g., Connolly & Doyle, 1984;Farver & Shin, 1997;Howes et al, 1989;Pellegrini & Perlmutter, 1989;Rubin & Maioni, 1975), but contrary to others (e.g., Lindsey & Mize, 2001;Rubin et al, 1978;Weinberger & Starkey, 1994), we found no gender differences in pretend play. Examination of the studies that have reported gender differences in pretend play reveal that most, although by no means all (see Jones & Glenn, 1991;Weinberger & Starkey, 1994, for exceptions), used semistructured and laboratory settings to observe children's play.…”
Section: Discussionsupporting
confidence: 83%
“…Some studies indicate that girls engage in more pretend play with peers than boys do (Jones & Glenn, 1991;Lindsey & Mize, 2001;Wall, Pickert, & Gibson, 1990;Weinberger & Starkey, 1994;Werebe & Baudonniere, 1991), whereas other studies indicate that boys engage in more pretend play with peers than girls do (Doyle, Ceschin, Tessier, & Doehring, 1991;Rubin, Maioni, & Hornung, 1976;Rubin, Watson, & Jambor, 1978;Singer, 1973). However, the majority of researchers report no differences in the amount of pretend play girls and boys engage in with peers (e.g., Connolly & Doyle, 1984;Farver & Shin, 1997;Howes, Unger, Seidner, 1989;Pellegrini & Perlmutter, 1989;Rubin & Maioni, 1975). As suggested by Goncu, Patt, and Kouba (2002), differences in methodologies or observational settings across studies may account for these discrepancies.…”
mentioning
confidence: 97%
“…Pretend play themes were coded to give a comparison of the content of pretense children and parents associate with imaginary companions because imaginary companions are themselves a form of elaborate pretense (Taylor, 1999). Categories of pretense themes were derived from Farver and Shin (1997) and consisted of (a) family interactions, (b) everyday activities, (c) danger in the environment, and (d) fantastic themes. In addition, activities were coded as to whether daily routines were mentioned (e.g.…”
Section: Imaginary Companion Questionsmentioning
confidence: 99%
“…One American study on 'social pretend play', with part Anglo and part South Korean-American 7-year-olds, provides supporting evidence (Farver and Shin 1997). South Korea has a MAS score of 39 and a GII 2014 of 23, both considerably lower than the USA.…”
Section: Culture and Playgroundsmentioning
confidence: 88%